Changes in sleep duration and 3-year risk of mild cognitive impairment in Chinese older adults - Zhu, Qi (Aging (Albany NY), 2020)
Objective: This study aimed to determine whether changes in sleep duration are associated with a higher risk of mild cognitive impairment (MCI) in older adults. Results: By the 3-year follow-up, 592 participants developed MCI. Compared with the individuals who had an unchanged sleep duration, the odds ratio (95% confidence interval) for MCI was 1.44 (1.08-1.91) for those whose sleep duration increased by ≥2 h after multivariate adjustments. Moreover, changing from a long to moderate, but not short, sleep duration was negatively associated with the incidence of MCI (odds ratio: 0.65; 95% confidence interval, 0.45-0.93). Conclusions: These findings suggest that increased sleep duration is associated with a higher risk of MCI in the elderly. Furthermore, a moderate duration of sleep (6-9 h) could serve as a possible strategy for prevention of MCI. Methods: This longitudinal study was conducted with a nationally representative sample of 5419 older Chinese adults (≥65 years) from the 2008 and 2011 waves of the Chinese Longitudinal Healthy Longevity Survey. Sleep duration was assessed by a self-administered questionnaire. MCI was defined according to the Mini-Mental State Examination. An adjusted logistic regression model was used to explore the associations between changes in sleep duration and MCI.